GIS-material for the archaeological project: A sill stone building and a deserted medieval farmstead by Herstadberg - Rebuilding of golf course in Herstadberg - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Norrköping municipality is planning for new industrial estates and road construction works by Herstadberg, Kvillinge parish, and for the moving and expansion of Ingelsta golf course. A previous archaeological assessment (phase 1) showed that there are several known archaeological sites within and nearby the survey area, as well as several areas which are likely to contain unmarked archaeological remains. A great number of trial trenches were dug during phase 2 of the assessment. Settlement remnants from the 17th or 18th century and what was probably a prehistoric hearth were found. To relate the remains closer to their context and dating, a more detailed analysis of historical maps was performed. The analysis showed that a farm has stood on the site, and that there are several abandoned building sites in the vicinity, deserted already in the 17th century and located on the site of the medieval farm Ströbo. The analysis also showed that the farms of Herstad village were not built on a common village site. Except for the remnants mentioned above no archaeological features or artefacts were found and no further archaeological investigations will thus take place on the site. The Herstad village site has kept the temporary designation UV 3, divided into UV 3a - c for the individual farms within the village. The deserted medieval farm of Ströbo has got the temporary designation UV 4, while waiting for an official ancient monuments record number.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the assessment (phase 2) was to determine whether or not the development area contained archaeological remains, and to document and, if possible, date the features and artefacts.

The ZIP file consists of shapefiles and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Norrköpings kommun planerar för industri- och vägbyggen vid Herstadberg, Kvillinge socken, Norrköpings kommun samt för flyttning och utvidgning av Ingelsta golfbana. En tidigare arkeologisk utredning, etapp 1, visade att det fnns kända fornlämningar inom och i anslutning till utredningsområdet liksom flera områden med topografiskt lämpliga boplats/gravlägen (Obj I-VI). Den nu aktuella utredningen, etapp 2, kom att omfatta Obj I - III. Ett stort antal sökschakt togs upp. Här påträffades bebyggelselämningar som troligen ska dateras till 16/1700-talet, samt en sannolikt förhistorisk härdgrop/ugnskonstruktion. För att knyta lämningarna till kontext och tidsperiod gjordes en utökad analys av historiskt kartmaterial. Analysen visade att det funnits en gård på platsen samt att det i närheten av detta område finns flera byggningstomter som är övergivna redan på 1600-talet, där en medeltida ödegård, Ströbo, har legat. Dessutom visade analysen att gårdarna i Herstad inte låg samlade inom en gemensam bytomt samt att det medeltida jordetalet "spanns avgäld" var i bruk ännu vid mitten av 1600-talet. Förutom de ovan nämnda byggnadslämningarna hittades inga anläggningar eller fynd. De nu upptäckta lämningarna är inte tillräckligt omfattande för att motivera ytterligare arkeologiska åtgärder på platsen. En revidering och tillägg till den tidigare registreringen av Herstads gamla bytomt (UV 3) gjordes också. I avvaktan på permanent fornlämningsnummer har benämningen UV 3 behållits, men delats upp i UV 3a - c för de olika gårdar som ingått i byn. Vidare antecknades den övergivna bytomten Ströbo som UV 4, Kvillinge sn.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen, etapp 2, var att konstatera om exploateringsområdet innehöll fornlämningar eller ej samt att dokumentera och om möjligt tidsbestämma anläggningar och fynd.

ZIP-filen innehåller shape-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: En syllstensbyggnad och en medeltida ödegård vid Herstadberg - Ombyggnad av golfbana inom Herstadberg
Keywords: 17th century; 1600-tal; 18th century; 1700-tal; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi